2015
DOI: 10.33549/physiolres.933110
|View full text |Cite
|
Sign up to set email alerts
|

How Hormones Influence Composition and Physiological Function of the Brain-Blood Barrier

Abstract: Hormones exert many actions in the brain. Their access and effects in the brain are regulated by the blood-brain barrier (BBB). Hormones as other substances may enter the brain and vice versa either by paracellular way requiring breaching tight junctions stitching the endothelial cells composing the BBB, or by passage through the cells (transcellular way). Hormones influence both ways through their receptors, both membrane and intracellular, present on/in the BBB. In the review the main examples are outlined h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It is reported that sex hormones exert a neuroprotective role that influences the permeability of the BBB. BBB cells play a complex role, ensuring the separation of circulating substances within the blood from nerve tissue, thus providing a well-balanced microenvironment in the brain [3]. In addition to endothelial cells, this role is also provided by other associated cells, including astroglia and pericytes [59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported that sex hormones exert a neuroprotective role that influences the permeability of the BBB. BBB cells play a complex role, ensuring the separation of circulating substances within the blood from nerve tissue, thus providing a well-balanced microenvironment in the brain [3]. In addition to endothelial cells, this role is also provided by other associated cells, including astroglia and pericytes [59].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic stress is frequently related to chronic pain conditions, such as fibromyalgia, irritable bowel syndrome, or neuropathic pain [1,2]. Pain conditions are neuroplastic alternations of the electrical properties that can cause increased excitability of neurons, as well as substantial changes in the permeability of the blood-brain barrier (BBB) [3][4][5]. Epidemiological studies and systematic reviews have pointed out a higher incidence of chronic pain conditions in women, but there is not enough information about the mechanisms underlying these sex-specific differences [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several more peptide hormone that are interacting with the BBB, for example ghrelin and leptin, which are among others responsible for hunger and homeostasis. The permeability of the BBB can be also influenced by cytokines, which are not crossing the BBB from the circulation, but are also expressed in the endothelial cells of the BBB and control the homeostasis of energy transfer(21). Thus the microbiome is able to change permeability.…”
mentioning
confidence: 99%